A Dendrite‐Structured RbX (X=Br, I) Interlayer for CsPbI2Br Perovskite Solar Cells with Over 15 % Stabilized Efficiency. Issue 20 (14th August 2020) - He, Jingjing; Ge, Bing; Hou, Yu; Yang, Shuang; Yang, Hua Gui
Abstract: Interface engineering has shown great potential to improve the photovoltaic performance and long‐term stability of perovskite solar cells. Herein, RbX (X=Br, I) materials were developed as the interfacial modifiers for CsPbI2 Br solar cells that realized power conversion efficiencies (PCE) over 15 % with a high open‐circuit voltage ( V OC ) of 1.27 V. The RbX interlayer having a dendrite‐shaped structure could optimize the surface wetting behavior of TiO2 films and thus enabled formation of high‐quality perovskite films. More importantly, RbX could better align the devices' energy levels and passivate surface defects because of its large bandgap. The PCE of a CsPbI2 Br device with RbX interlayer remained 87 % of its initial efficiency for 800 h in ambient atmosphere. Abstract : Ruby sparkles in the sun : A dendrite‐structured RbX (X=Br, I) interlayer is prepared for use in CsPbI2 Br solar cells via a simple solution process. Such dendrite‐structured interlayer could provide the formation of high‐quality perovskite films that realize high power conversion efficiencies over 15 % of CsPbI2 Br solar cells.